Gender, Metal and the Media: An Introduction - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Hill offers a much needed discussion of the lack of consideration given to gender in academic discussions of hard rock and metal music and the media. Drawing on her own experience as a musician and fan, the author argues that orthodoxies—e.g., the genre is inclusive, the music asexual and sexism non-existent—are only able to persist within the literature because scholars have neglected to understand how musical experiences are gendered. Within the context of feminist popular music scholarship, work on fandom and feminist methodological work, Hill outlines the need to study hard rock, metal and the media with close attention to the influence of gender.
Keywords: Black Metal; Hard Rock; Metal Music; Rock Music; Social Expression

Listening to Hard Rock and Metal Music - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
This chapter challenges readings of hard rock and metal as masculine music. Hill examines women’s accounts of their experiences of musical pleasure. Through analysis of women fans’ descriptions of their favourite bands, she argues that, pace Kahn-Harris (2007), fans can be very articulate about what they like. Work of feminist writers on rock music is enlisted to argue that considering women’s listening pleasure gives new insights into the meaning of hard rock and metal music. The assumption that hard rock and metal is a masculine genre neglects important aspects of women’s fandom which diverge from the dominant myths.
Keywords: False Consciousness; Hard Rock; Heavy Metal; Musical Experience; Rock Music